1992
DOI: 10.1093/ajh/5.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Levels of Endothelin in Diabetic Patients With Hypertension: An Alternative Viewpoint

Abstract: In order to gain insight into the potential role of endothelin, a 21 amino acid peptide produced by endothelial cells, in the development of complications of diabetes mellitus, basal plasma endothelin levels were measured in 152 patients with diabetes mellitus (83 patients with type 1 diabetes mellitus, 69 patients with type 2 diabetes mellitus) and compared to those in 50 healthy controls. Blood was drawn at 8:00 AM under resting conditions and endothelin was measured after prior extraction by a sensitive rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 9 publications
4
37
2
6
Order By: Relevance
“…Earlier studies have shown that circulatory levels of ET-1 are increased in obesity. 10,[20][21][22][23][24] We have recently shown that s.c. adipose tissue, which is the major adipose region, might contribute to the elevated levels of ET-1 in the obese state. 10 This study shows that the expression of ET-1 mRNA is higher in s.c. adipose tissue compared with OM adipose tissue, whereas ETR expression is similar in the two depots .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that circulatory levels of ET-1 are increased in obesity. 10,[20][21][22][23][24] We have recently shown that s.c. adipose tissue, which is the major adipose region, might contribute to the elevated levels of ET-1 in the obese state. 10 This study shows that the expression of ET-1 mRNA is higher in s.c. adipose tissue compared with OM adipose tissue, whereas ETR expression is similar in the two depots .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 (ET-1) is not only one of the most potent vasoconstrictors but it also has pro-inflammatory and profibrotic effects, which may contribute to the pathogenesis of nephropathy. In the previous studies, it was demonstrated that serum ET1 level was increased in diabetic patients with microalbuminuria, retinopathy or higher glycosylated hemoglobin (HbA1c) (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma ET-1 levels are increased in the diabetic state (Takahashi et al, 1990;Makino & Kamata, 1998;Makino et al, 2001) and the plasma concentration of big endothelin-1, the precursor of ET-1, is elevated in patients with diabetes mellitus (Tsunoda et al, 1991). Thus, although ET-1 may also contribute to the normal maintenance of vascular tone, a pathogenetic role is implied by its overproduction in patients with diabetes (Takahashi et al, 1990;Haak et al, 1992).…”
Section: Introductionmentioning
confidence: 99%